2021
DOI: 10.29244/jfs.v6i1.35796
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Quality of Life on Farmer Family: Roles of Gender Relations, Economic Pressure, Financial Management, and Livelihood Strategies

Abstract: Indonesia as the largest tropical agricultural countries support natural conditions make Indonesia a country rich in agricultural products. The objective of this research was to analyze the influence of economic pressures, financial management, gender relations, and livelihood strategies toward the farmer families quality of life. This research used a quantitative study design. The research took place in West Java. Sixty respondents were chosen from the farmer's wife that selected by using a simple random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Apart from that, low-income families tend not to manage their finances well due to irregular income. Low-income families go through a process that is not based on a written record of what they planned, but on experience and routine (Herawati et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, low-income families tend not to manage their finances well due to irregular income. Low-income families go through a process that is not based on a written record of what they planned, but on experience and routine (Herawati et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the need for health funds has also increased, especially if there are families affected by the coronavirus. Research by D'Rummo, Miller, TenNapel, and Shen (2020), Kumalasari (2021), andSpencer et al (2017) found that a decreased QoL could be caused by a poor way of managing family finances because it had an impact on low family survival. Previous research also said that the QoL is measured by financial behavior, life satisfaction, and physical health (Curran, Parrott, Ahn, Serido, & Shim, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In going through the difficult times of the Covid-19 pandemic, families are required to be able to survive in carrying out their daily lives by utilizing gender roles partnerships (Kasdi & Saifudin, 2020). The results of Herawati, Simanjuntak, and Kumalasari (2021) research found that families who apply good gender relations have a good livelihood strategy. Families who have a good livelihood strategy have a low risk of experiencing economic pressure.…”
Section: Introductionmentioning
confidence: 99%